PROFESSIONAL ETHICS OF A PSYCHOLOGIST AS A SUBJECT OF RESEARCH IN A LEGAL SCIENCES - Makeieva, Olena; Boiko, Oleg (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: to investigate modern scientific approaches to the study of the notary institution in the system of protection of human and citizen rights and freedoms. Research methods: analysis, synthesis, generalization, historical, comparative legal, philosophical. Results: based on the analysis of scientific literature, a periodization of the genesis of scientific research of the notary institute was proposed, the main directions and problems studied were highlighted. It has been established that the institution of notary is a part of the historical and legal process directly related to the establishment of notarial activity. Discussion: the notary institute promotes the protection of the rights of individuals and legal entities, provides qualified legal assistance on the basis of equality, legality and justice, prevents the emergence of legal conflicts in the field of civil turnover. In modern conditions, it is necessary to understand the valuable principles of the notary institution, its content, purpose and legal regulation. It is also worth solving the issue of improving the conceptual and categorical apparatus of the notary institution in the system of human rights protection and its functioning in the conditions of modern challenges and threats. This issue is especially relevant during the legal regime of martial law in Ukraine, when human rights are often violated. The analysis of the genesis of scientific research of the notary institute in the system of human rights protection is gaining relevance and requires both scientific and applied study. The functioning of the notary institution is determined by the interaction of two factors: on the one hand, it is a subjective personal right of a person, and on the other, guarantees of protection of rights and freedoms. In this aspect, the right to qualified legal assistance as a subjective right is understood as a legally guaranteed opportunity for a person to receive the help he needs from persons who have special legal knowledge, skills and abilities, which enables a person to effectively protect and defend his rights and legitimate interests. The study of the notary institution in the system of protection of the rights and freedoms of a person and a citizen determines, first of all, changes in the general system of methodology for the study of individual legal phenomena. The Institute of Notaries is an important human rights institution that guarantees the legality of the rights and interests of individuals and legal entities. An important aspect of the work of notarial bodies is a clearly regulated notarial procedure, which is provided by the state for the legal exercise of their rights by individuals.